The three-step persuasion model on YouTube: A grounded theory study on persuasion in the protein supplements industry - Tripathi, Jayanshi; de Vries, Roelof A. J.; Lemke, Mailin (Frontiers in Artificial Intelligence, 2022)
Persuasion can be defined as an active attempt by a person to change the behavior and attitudes of others. Social media platforms provide individuals with the opportunity to observe the behavior of others and imitate it. By strategically altering the publicly displayed behavior on social media, influencers can persuade the observers (the social media content consumers) to adopt certain desirable behavior. The aim of this research is to understand persuasive techniques used by health professionals on YouTube to promote the use of protein supplements. The research adopts the interpretive paradigm and will use qualitative data analysis through interpretive grounded theory. Through a combination of theoretical, purposive, and convenience sampling, we selected 60 YouTube videos. Our results show that on YouTube, persuasion can be dissected into three steps: reaching the message, staying on the message, and performing the action desired by the persuader. We discovered five core themes - quality, curiosity, engagement, concretization, and genuineness - that contributed to the persuasiveness of the analyzed YouTube videos. The chief finding of this research is a three-step model of persuasion for YouTube videos. The model has implications in the design of persuasive interfaces and applications for positive behavioral change. We also discuss the similarities between the proposed model and the existing literature on persuasion. Finally, based on interviews with subject experts, we describe the limitations and possible future work directions of this research.